Ultrasound in inflammatory and obstructive salivary gland diseases: Own experiences and a review of the literature - Koch, Michael; Sievert, Matti; Iro, Heinrich; Mantsopoulos, Konstantinos; Schapher, Mirco (Journal of Clinical Medicine, 2021)
Background: Ultrasound is established as a diagnostic tool in salivary glands for obstructive diseases such as sialolithiasis and tumors. Concerning inflammatory diseases and in non-sialolithiasis-caused obstruction, much fewer data are available. In recent years, technical devel-opment has allowed a better assessment of the gland parenchyma, and knowledge about intraductal pathologies has increased considerably, which has provided new insights and a new interpretation of ultrasound findings. Objectives: To provide a comprehensive review of the literature that in-cludes our own experiences and to point out the state of the art in ultrasound in the diagnostics of inflammatory and obstructive salivary gland diseases, taking adequate techniques and recent technical developments into consideration. Data sources and study eligibility criteria: A systematic literature search was performed in Pubmed using various specific key words. Results: According to the literature results, including our own experiences, ultrasound is of value in up to >90% of cases presenting with inflammatory and/or obstructive diseases. Technical developments (e.g., elastography) and the application of modified ultrasound techniques (e.g., transoral ultrasound) have contributed to these results. Today, ultrasound is considered a first-line diagnostic tool in these diseases. However, in some inflammatory diseases, the final diagnosis can be made only after inclusion of the anamnesis, clinical symptoms, serologic blood tests, or histopathologic investiga-tion. Conclusions: Ultrasound can be considered as a first-line diagnostic tool in obstructive and inflammatory salivary gland diseases. In obstructive diseases, it may be sufficient for diagnostics in >90% of cases. In inflammatory diseases, ultrasound is at least an excellent screening method and can be used to establish the diagnosis in cases of an early suspicion. In all diseases ultrasound can contribute to better management and can be used for monitoring during follow-up.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Inflammatory; Obstructive; Salivary calculi; Salivary gland; Salivary gland diagnosis; Salivary gland disorders; Salivary ultrasonography; Sialadenitis